Critical analysis of endometriosis surgery as a treatment for infertility (Research, Society and Development, 2023)
Endometriosis is a chronic inflammatory disease caused by the presence of endometrial tissue outside the uterus that may manifest asymptomatically or cause symptoms such as dysmenorrhea, dyspareunia, abnormal bleeding, and/ or infertility The treatment of choice is based on symptomatology, and surgery is among the most used treatments. This study aims to analyze which patient actually benefits from endometriosis surgery as a treatment for infertility. In this regard, a literature review was made of articles that approach this subject, which was researched in databases through the descriptors "infertility" or "endometriosis" or "surgery", initially bringing important concepts and classifications about the disease and its relationship with infertility. In conclusion, by comparing the results of the articles studied, it is expected to indicate the appropriate management in relation to infertility and to evaluate when the surgery will really bring benefits, avoiding subjecting patients to an invasive procedure without obtaining the appropriate result or even causing damage that affects them your quality of life.